A Network Pharmacology-Based Study on Irritable Bowel Syndrome Prevention and Treatment Utilizing Shenling Baizhu Powder. (23rd November 2021) - Meng, Meng; Bai, Chen; Wan, Bo; Zhao, Luqing; Li, Zhe; Li, Danyan; Zhang, Shengsheng
Abstract : Background and Objective . Irritable bowel syndrome (IBS) is a prevalent disorder of the gastrointestinal system with complex pathogenesis. Shenling Baizhu powder (SLBZP) is a Chinese herbal compound with multicomponent and multitarget characteristics. Increasing volumes of evidence demonstrate that it has a notable therapeutic impact on IBS. This study therefore is aimed at exploring the potential effective components of SLBZP and their mechanisms in IBS treatment utilizing network pharmacology. Methods . Metabolomics was used to detect the secondary metabolites in SLBZP; the target protein was acquired by target fishing according to the compound's structure. The SymMap database was used to search herbal medicines for the target protein. The target gene of IBS gave rise to the common gene protein which is the potential target of SLBZP in IBS therapy. The interactions between target proteins were analyzed in a STRING database, the protein relationship network was analyzed using Cytoscape software, and the Kyoto Encyclopedia of Genes and Genomes enrichment analysis of the core target gene group was carried out in a DAVID database in order to construct the "compound-traditional Chinese medicine/molecule-target-pathway" network. Molecular docking was used to verify the core protein and its related small molecular compounds. Result . There were 129 types of secondary metabolites in SLBZP. 80 target proteins of these metabolites were potential core targets for IBS treatment including acetylcholinesterase (AChE), arachidonate-5-lipoxygenase (ALOX5), B-cell lymphoma-2 (BCL2), recombinant cyclin D1 (CCND1), and catenin- β 1 (CTNNB1), among others. Results from these targets indicated that the most enriched pathway was the tumor necrosis factor (TNF) signaling pathway (p < 0.001 ) and that the most abundant pathway was signal transduction. In the network nodes of the TNF signaling pathway, the Chinese medicines with the highest aggregation were Lablab semen album and Glycyrrhizae radix et rhizoma (degree = 11 ). The small molecules with the highest aggregation were oxypeucedanin and 3, 5, 6, 7, 8, 3 ′, 4 ′ -heptamethoxyflavone (degree = 4 ). Molecular docking results confirmed that daidzein 7-O-glucoside (daidzin) had the highest degree of binding to TNF proteins in the TNF signaling pathway. Conclusion . This study shows that SLBZP can treat IBS by influencing multiple targets and pathways, of which the TNF signaling pathway may be the most significant. This typifies the pharmacological characteristics of traditional Chinese medicine, i.e., multiple targets, numerous pathways, and specific therapeutic effects on diseases. SLBZP can therefore be used as a candidate drug for clinical IBS by intervening in human signal transduction.